MISINTERPRETATIONS OF REAL NEEDS IN SL AND FL WRITING SITUATIONS: IS THERE A NEED TO RE-EVALUATE DIRECTIONS? - Jayakaran Mukundan (Indonesian JELT, 2006)
Teachers of English in Second language and foreign language situations who teach writing have had to face many challenges, some of which have come about from rapid changes in the teaching of writing in the developed nations. The dilemma that teachers face is a big one – whether to totally embrace the changes (which are advocated by these developed nations as being necessary to achieve better teaching and learning, or to adopt and adapt where necessary. This article provides the over-view of problems faced by writing teachers in SL/FL situations and provides some suggestions as to how teachers can deal with “paradigm shifts” as in the ones that have affected the field of writing. Keywords:   composing, compositions, culture, directions, discourse communities, learning style preferences, misinterpretations, revolution, paradigm shift, process, product, writing